Ralf Dahrendrotf’s Analytical Categories - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2007)
The aim of the article is to identify and critically assess the key concepts, ideas and the epistemological principles of Ralf Dahrendorf as a theorist of social conflict. Dahrendorf tries to combine the insights of Marxian sociology with the new 20th century realities and develops the beginnings of a systematic theory of conflict which emphasizes the existence of a plurality of “imperatively coordinated associations” and therefore of conflicting classes engendered by them. The article goes on to show how the conceptual framework of Dahrendorf can be more fruitfully pursued by emphasizing that Marx’s notion of social class is not so outmoded, and specifying the conceptual connections between the various class definitions and criteria.
Keywords: Ralf Dahrendorf; social conflict; authority; social role; imperatively coordinated associations; class definitions and criteria